Knowledge mobilisation in practice: an evaluation of the Australian Prevention Partnership Centre - Abby Haynes; Samantha Rowbotham; Anne Grunseit; Erika Bohn-Goldbaum; Emma Slaytor; Andrew Wilson; Karen Lee; Seanna Davidson; Sonia Wutzke (BMC, 2020)
Abstract Background Cross-sector collaborative partnerships are a vital strategy in efforts to strengthen research-informed policy and practice and may be particularly effective at addressing the complex problems associated with chronic disease prevention. However, there is still a limited understanding of how such partnerships are implemented in practice and how their implementation contributes to outcomes. This paper explores the operationalisation and outcomes of knowledge mobilisation strategies within the Australian Prevention Partnership Centre - a research collaboration between policy-makers, practitioners and researchers. Methods The Centre's programme model identifies six knowledge mobilisation strategies that are hypothesised to be essential for achieving its objectives. Using a mixed methods approach combining stakeholder interviews, surveys, participant feedback forms and routine process data over a 5-year period, we describe the structures, resources and activities used to operationalise these strategies and explore if and how they have contributed to proximal outcomes. Results Results showed that Centre-produced research, resources, tools and methods were impacting policy formation and funding. Policy-makers reported using new practical methodologies that were helping them to design, implement, evaluate and obtain funding for scaled-up policies and programmes, and co-creating compelling prevention narratives. Some strategies were better implemented and more impactful than others in supporting these outcomes, with variation in who they worked for. The activities used to effect engagement, capacity-building and partnership formation were mostly generating positive results, but co-production could be enhanced by greater shared decision-making. Considerably more work is needed to successfully operationalise knowledge integration and adaptive learning. Conclusions Describing how collaborative cross-sector research partnerships are operationalised in practice, and with what effects, can provide important insights into practical strategies for establishing and growing such partnerships and for maximising their contributions to policy. Findings suggest that the Centre has many strengths but could benefit from more inclusive and transparent governance and internal processes that facilitate dialogue about roles, expectations and co-production practices.